Targeting GPCRs to treat cardiac fibrosis - Zhang, Hao; Ren, Lu; Shivnaraine, Rabindra Vishwadev (Frontiers in Cardiovascular Medicine, 2022)
Cardiac fibrosis occurs ubiquitously in ischemic heart failure, genetic cardiomyopathies, diabetes mellitus, and aging. It triggers myocardial stiffness, which impairs cardiac function, ultimately progressing to end-stage heart failure and increased mortality. Although several targets for anti-fibrotic therapies have been identified, including TGF-β and receptor tyrosine kinase, there is currently no FDA-approved drug specifically targeting cardiac fibrosis. G protein-coupled receptors (GPCRs) are integral, multipass membrane-bound receptors that exhibit diverse and cell-specific expression, offering a novel and unrealized therapeutic target for cardiac fibrosis. This review highlights the emerging roles of several GPCRs and briefly explores their downstream pathways that are crucial in cardiac fibrosis. We provide an overview of GPCRs expressed on cardiac fibroblasts directly involved in myofibroblast activation and describe those GPCRs contributed to cardiac fibrosis via indirect crosstalk mechanisms. We also discuss the challenges of identifying novel effective therapies for cardiac fibrosis and the strategies to circumvent these challenges.